The Micro Origins of International Business-Cycle Comovement - di Giovanni, Julian; Levchenko, Andrei A.; Mejean, Isabelle (American Economic Review, 2018)
This paper investigates the role of individual firms in international business-cycle comovement using data covering the universe of French firm-level value added and international linkages over the period 1993–2007. At the micro level, trade and multinational linkages with a particular foreign country are associated with a significantly higher correlation between a firm and that foreign country. The impact of direct linkages on comovement at the micro level has significant macro implications. Without those linkages the correlation between France and foreign countries would fall by about 0.098, or one-third of the observed average correlation of 0.291 in our sample of partner countries. (JEL F14, F23, F44, F62, L14)